Pengaruh chronotype dan tingkat stres terhadap status gizi dengan mediator perilaku makan pada mahasiswa perkuliahan daring - Tesa Rafkhani; Mohammad Fanani; Adi Magna Patriadi Nuhriawangsa (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
The effect of chronotype and stress levels on nutritional status mediated by eating behavior in college students with online lectureBackground: College students are a group at risk of experiencing changes in stress levels, changes in eating behavior, and sleep quality. Unhealthy eating behavior, if done continuously, will lead to weight gain.Objective: This study aims to analyze the effect of chronotype and stress levels on nutritional status mediated by the eating behavior of college students with online lectures.Methods: Cross-sectional survey with multistage cluster random sampling on 220 respondents. Chronotype data used by Morningness - Eveningness Questionnaire (MEQ). Stress level data using by Perceived Stress Scale (PSS-10) questionnaire. Eating behavior data was used by Dutch Eating Behavior Questionnaire (DEBQ). Nutritional status data is measured according to body mass index (BMI) by measuring weight (kg) and height (m2). Data were analyzed using Partial Least Square-Structural Equation Model (PLS-SEM) analysis using SmartPLS software.Results: The results showed that there was a significant indirect effect between chronotype (x1) on nutritional status (y2) mediated by eating behavior (p=0.037) with an impact of 0.085 or 8.5%. In comparison, the magnitude of the direct effect without a mediator was 0.193 or 19.3%. Furthermore, there is a significant indirect effect between stress level (x2) on nutritional status (y2) mediated by eating behavior (p=0.017) with an impact of 0.074 or 7.4%. The direct effect without a mediator is 0.217 or 21.7%.Conclusions: There is a significant indirect effect between chronotype and stress level on nutritional status mediated by eating behavior in students with online lectures. During the COVID-19 pandemic, college students should continue to pay attention to healthy eating behavior by preventing emotional eating, setting bedtime earlier, and avoiding stress by increasing physical activity.